(untitled) (Damascus University Journal for legal sciences, 2026)
During the crisis, the Syrian Arab Republic faced many internal and external challenges, especially the problem of the deficit in the general budget, especially after it reached levels that threatened the financial and monetary stability of the state and the resulting various effects of a continuous deterioration in the purchasing power of the national currency of the state, and a deterioration in the level of The livelihood of the citizen, which put pressure on the public budget, andpleted the reserves and external assets. The Syrian crisis has greatly affected the high deficit rates in the general budget, due to the significant deterioration in public revenues, whether oil or tax, and the stopping of many economic establishments from working, in addition to the unilateral economic coercive measures imposed by European countries, and the inability to access markets. Global finance, government corruption that found its appropriate climate in these exceptional circumstances through tax evasion and administrative sluggishness in state institutions, and the absence of any effective oversight by government agencies and legislative councils over public money. All of these aforementioned reasons exacerbate the deficit problem in the general budget of the Arab Republic . The Syrian government, in light of this situation, is forced and has no choice in using deficit funding.